Subjective preference of new prototypes safety helmets device among palm oil plantation harvesters in Sandakan, Sabah - Nazri, Nur Al - Izzah; Mohd Tamrin, Shamsul Bahri; Mohd Suadi Nata, Dayana Hazwani; Ng, Yee Guan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Safety helmets are one of the personal protective equipment (PPE) that to decrease the impact of any falling object to the skull and to avoid head and brain injury by many industries, including palm oil plantation. Nevertheless, the level on the usage of the current safety helmet is very low due to a few factors that lead to the discomfort. Among the common issues for the non-compliance of safety helmets are their discomfort, ventilation, weight and safety. This study aims to determine subjective preference of the new prototypes’ safety helmets device among palm oil plantation harvesters. Methods: A cross-sectional study conducted among 124 harvesters in three palm oil plantations located in Sabah, Malaysia. A set of questionnaires used to collect data on their socio-demographic background, perceptions toward existing safety helmets and their subjective preference of new safety helmets prototypes. Apart from that, six harvesters were randomly choosing to attend an interview session for qualitative study. Results: The descriptive analysis indicate that among the emphasized issues regarding non-compliance of existing safety helmet were due to discomfort (66.1%), poor ventilation (97.6%), load of safety helmet (83.3%) and safety issues (68.5%). In terms of new safety helmets prototypes, 72.6% of the harvesters preferred Design C to be worn for work in the plantation. Conclusion: It can be suggested that the existing safety helmet is uncomfortable and was not design ergonomically namely loose size and discomfort. Design C was the most preferred to be worn for work in the palm oil plantation.